2001
DOI: 10.1152/ajpheart.2001.281.6.h2697
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular systolic function in young lambs subject to chronic systemic right ventricular pressure overload

Abstract: In various clinical situations of congenital heart disease, the right ventricle (RV) is subject to a chronic systemic pressure overload which affects biventricular function and may progress to the development of RV failure. Young lambs (2-3 wk old) underwent adjustable pulmonary artery banding (PAB) at systemic (aortic) level for 8 wk. Biventricular function was determined by using load-independent indexes of global ventricular contractile performance by the end-systolic pressure-volume relationship (ESPVR) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 42 publications
5
53
2
Order By: Relevance
“…Surprisingly, this did not occur because of simultaneous development of left ventricular hypertrophy. While previous bi-ventricular conductance catheter studies in lambs showed impairment of left ventricular function during right ventricular hypertrophy (Leeuwenburgh et al, 2001), our findings showing that banded animals displayed significant bilateral hypertrophy, with potential biventricular increase of systolic function in terms of myocardial systolic thickening. The design of our study, however, however, does not permit us to speculate regarding the mechanism responsible for this phenomenon.…”
Section: Considerations Regarding the Modelcontrasting
confidence: 89%
See 1 more Smart Citation
“…Surprisingly, this did not occur because of simultaneous development of left ventricular hypertrophy. While previous bi-ventricular conductance catheter studies in lambs showed impairment of left ventricular function during right ventricular hypertrophy (Leeuwenburgh et al, 2001), our findings showing that banded animals displayed significant bilateral hypertrophy, with potential biventricular increase of systolic function in terms of myocardial systolic thickening. The design of our study, however, however, does not permit us to speculate regarding the mechanism responsible for this phenomenon.…”
Section: Considerations Regarding the Modelcontrasting
confidence: 89%
“…Other experimental models have been proposed (Leeuwenburgh et al, 2001). It is not surprising, therefore, that we were able to develop our model on the basis of growth-induced relative stenosis.…”
Section: Considerations Regarding the Modelmentioning
confidence: 89%
“…Interestingly, both RV and LV chamber volumes were diminished in this group of patients. These findings are similar to experimental studies performed in sheep after 2 months of pulmonary stenosis, 3 whereas studies involving adult patients with prolonged increased RV afterload demonstrated a progressive dilation of RV volumes. 27 Although further studies are needed to elucidate underlying mechanisms, it may be hypothesized that small RV volumes, as noted in the present study, are due to a combination of limited diastolic filling in the presence of eccentric myocardial hypertrophy and enhanced myocardial contractile performance.…”
Section: Physiological Aspects Of This Studysupporting
confidence: 87%
“…16 More recently, several animal and human conductance catheter studies were reported for analysis of RV function. 3,5,7 However, the assessment of the trapezoidal RV or morphologically deformed ventricle, existent in many patients with congenital heart disease, can be problematic because of field inhomogeneities and mismatch between catheter segments and the RV cavity. In addition, the use of conductance catheters is time consuming and requires added radiation exposure; therefore, conductance catheters are used predominantly as a research tool, not in routine clinical practice.…”
Section: Technical Aspects Of This Studymentioning
confidence: 99%
See 1 more Smart Citation